1971
DOI: 10.2466/pms.1971.33.3.859
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Study of Reality Testing in Schizophrenics

Abstract: Perky's (1910) method of studying perception and imagery was adapted to study reality testing in schizophrenia. 10 schizophrenic and 10 non-schizophrenic Ss were seen in 2 identical sessions during which they were asked ' t o differentiate between sounds they imagined and sounds they heard through earphones. The schizophrenic Ss, although reporting fewer images, manifested more perceptual distortions and more misperceptions of actual sounds ar images. The procedure described seems to hold promise as both a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In addition to establishing that auditory images are the primary mode of hallucination and that both schizophrenics and normals experience the same types and frequency of mental images, the majority of research in this area strongly support Mintz and Alpert's findings (Beck, 1970;Malitz et al, 1962;Mintz, 1971;Roman & Landis, 1968;Shapiro, 1972;Silverman et al, 1971;Spanos & Barber, 1968). The closest phenomenon to the psy chotic experience of imagery is "runaway imagery," a bad experience that is occasionally encountered in systematic desensitization and implosive ther apy (Barrett, 1969(Barrett, , 1970.…”
Section: Psychodiagnosis and Psychopathologysupporting
confidence: 51%
See 1 more Smart Citation
“…In addition to establishing that auditory images are the primary mode of hallucination and that both schizophrenics and normals experience the same types and frequency of mental images, the majority of research in this area strongly support Mintz and Alpert's findings (Beck, 1970;Malitz et al, 1962;Mintz, 1971;Roman & Landis, 1968;Shapiro, 1972;Silverman et al, 1971;Spanos & Barber, 1968). The closest phenomenon to the psy chotic experience of imagery is "runaway imagery," a bad experience that is occasionally encountered in systematic desensitization and implosive ther apy (Barrett, 1969(Barrett, , 1970.…”
Section: Psychodiagnosis and Psychopathologysupporting
confidence: 51%
“…Beck (1970) There has been much written about the role of imagery in the psycho ses. In 1917 Freud noted that the essence of reality testing (a diagnostic factor) was the ability to distinguish images from actual perceptions (Silverman, Pettit, Goldweber, & Spiro, 1971). Lending research support to Freud, Mintz and Alpert (1972) have demonstrated that schizophrenics expe rience vivid imagery and that their reality testing is impaired.…”
Section: Psychodiagnosis and Psychopathologymentioning
confidence: 99%